Konten Keislaman dalam Aplikasi Edukatif sebagai Media Komunikasi Keluarga - Pambudi, Buyung; Nunung Prajarto; Budi Irawanto (Jurnal Komunikasi Islam, 2023)
This research aims to examine the usage of digital applications for educational purposes produced in Indonesia and containing Islamic messages in order to improve family communication. This study used a descriptive qualitative method and considered Educa Studio and Solite Kids applications as research objects. The results of this research state that these two digital applications provide benefits for intensifying communication among family members, between parents and children in particular. In addition, the Islamic content within educational games in both the Educa Studio and Solite Kids applications is a means of spreading Islamic values from an early age. In short, through these digital applications, the intensity of interaction between children and parents can prevent children's accessibility to negative media contents that are not in accordance with Islamic religious values.